Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas Terhadap Nilai Perusahaan dengan Kebijakan Dividen Sebagai Variabel Moderating pada Perusahaan Makanan dan Minuman yang Terdaftar di Indeks Saham Syariah Indonesia - Agung Wiyono (Economic Reviews Journal, 2026)
This study aims to examine the effects of liquidity, solvency, and profitability on firm value, with dividend policy serving as a moderating variable, in food and beverage companies listed on the Indonesia Sharia Stock Index (ISSI) during the 2020–2024 period. A quantitative approach was employed using the Moderated Regression Analysis (MRA) method. The sample consisted of 24 companies selected through purposive sampling. The findings reveal that liquidity and solvency have no significant effect on firm value, whereas profitability has a positive and significant effect. Furthermore, dividend policy does not moderate the relationship between liquidity, solvency, or profitability and firm value. These results indicate that profitability is the primary factor influencing investors' assessment of firm value in sharia-compliant food and beverage companies, while liquidity, solvency, and dividend policy do not significantly contribute to enhancing firm value. The findings imply that companies should prioritize improving profitability as a strategy to increase firm value in the Islamic capital market.